Global Climate Change Mitigation, Fossil-Fuel Driven Development, and the Role of Financial and Technology Transfers : A Simple Framework - Wiegand, Johannes (IMF Working Papers; Working Paper ;, 2021)
Climate financing and compensation have emerged as key themes in the international climate mitigation debate. According to one argument in support of compensation, advanced economies (AEs) have used up much of the atmosphere's absorptive capacity, thus causing global warming and blocking a similar, fossil-fuel driven development path for emerging markets and developing economies (EMDEs). This paper develops a simple model of a sequential, fossil-fuel driven development process to discuss these issues systematically. The results suggest: (i) AEs have typically a stronger interest in climate change mitigation than EMDEs, (ii) from an equity perspective, compensation is called for only if EMDEs are relatively small; (iii) there can also be an efficiency case for compensation, however, with AEs buying EMDEs out of some of their GHG emissions; (iv) ultimately, a superior option-for both the world's climate and growth prospects-is the development of clean energy technologies by AEs and their transfer to EMDEs. The latter requires strong mitigation efforts by AEs even if EMDEs fail to play along initially.